A systematic review and meta-analysis on effect of beta-blockers in severe traumatic brain injury (2021)
Objectives: Systematically review the medical literature for the impact of beta-blockers on mortality and functional capacity in patients who suffered severe traumatic brain injury. Data Sources: The search included MEDLINE, EMBASE, and Ovid Evidence-Based Medicine, clinical trial registries, and bibliographies. Study Selection: All articles that reported outcome in TBI patients treated with beta-blockers. Data Extraction: Publication year, number of patients, outcome and follow-up. We performed a meta-analysis for each variable for which there were sufficient data to estimate mean differences. Data Synthesis: 12 studies were included, which involved retrospectively and prospectively collected data on 14,057 patients. The treatment with beta-blockers was associated with a reduction in mortality in patients who were treated with beta-blockers compared to the control group (OR 0.40, 95% CI 0.30–0.54p = <0.00001), with acceptable heterogeneity between studies (I2 = 65% p = 0.00008). Beta-blocker therapy decreases the risk of negative neurological and functional outcomes (OR 0.59, 95% CI 0.38–0.92 p = <0.00001), a very high statistical heterogeneity between the included studies (I2 = 80% p = 0.00004), being able to influence the results. An increase in favorable neurological and functional outcomes is shown (OR 1.19, 95% CI 1.07–1.31 p = 0.001) with acceptable heterogeneity (I2 = 52% p = 0.08) Conclusions: The beta-blockers therapy is associated with significantly improves outcome in patients with TBI. Treatment with beta-blockers in patients with TBI is a promising frontier in neurotrauma. Abbreviations:CI: confidence interval; BB: Beta-Blockers; OR = odds ratio; TBI: Traumatic Brain Injury SD: Standard deviation; SNS: Sympathetic nervous system